Penguatan Kewenangan Dewan Perwakilan Daerah (DPD) sebagai Representasi Daerah dalam Sistem Legislasi Nasional - Mustari, Rizal Fahmi; Ruslie, Ahmad Sholikhin (Media Hukum Indonesia (MHI), 2026)
The Regional Representative Council (DPD) was established through an amendment to the 1945 Constitution as a form of regional representation in the Indonesian constitutional system. However, the legislative authority granted to the DPD is very limited and therefore not commensurate with the electoral legitimacy it obtains through direct elections by the people in each province. This gap between legitimacy and authority creates a representation problem, especially because all laws inherently impact the regions, thus affecting the DPD's role only on regional issues, which are no longer constitutionally or practically relevant. Constitutional Court Decisions No. 92/PUU-X/2012 and 79/PUU-XII/2014 have affirmed the DPD's equal standing with the President and the House of Representatives in the submission and deliberation stages of certain bills. However, its implementation has been hampered by political resistance and regulations, particularly through the MD3 Law which reduces the DPD's constitutional authority. This study uses a normative juridical method with a regulatory, conceptualization, and case approach to assess the urgency of strengthening the DPD's authority as part of the checks and balances mechanism in the legislative system. The research findings indicate that strengthening the authority of the Regional Representative Council (DPD) through granting veto power for regional-related bills and mandatory involvement in all bill deliberations, even without the right to vote, is a constitutional and political necessity to ensure effective regional representation, strengthen national integration, and balance the House of Representatives' dominance in lawmaking.